Obtaining the structure factors for an epitaxial film using Cu X‐ray radiation. (25th October 2013) - Wadley, P.; Crespi, A.; Gázquez, J.; Roldán, M.A.; García, P.; Novak, V.; Campion, R.; Jungwirth, T.; Rinaldi, C.; Martí, X.; Holy, V.; Frontera, C.; et al.
<x xml:space="preserve">Abstract</x> Determining atomic positions in thin films by X‐ray diffraction is, at present, a task reserved for synchrotron facilities. Here an experimental method is presented which enables the determination of the structure factor amplitudes of thin films using laboratory‐based equipment (Cu Kα radiation). This method was tested using an epitaxial 130 nm film of CuMnAs grown on top of a GaAs substrate, which unlike the orthorhombic bulk phase forms a crystal structure with tetragonal symmetry. From the set of structure factor moduli obtained by applying this method, the solution and refinement of the crystal structure of the film has been possible. The results are supported by consistent high‐resolution scanning transmission electron microscopy and stoichiometry analyses.